KAJIAN ASURANSI SYARIAH DALAM EKONOMI ISLAM - Safwan Safwan; Nursari Dewi M (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2018)
Human life in this world is surrounded by various threats of danger that always provoke fear and hysteria. The threat of this danger always comes and goes and is difficult to calculate, so people must create innovation to get a sense of security and peace and to avoid the selaksa of danger that envelop life. One of them by establishing an insurance company. Insurance as a non-bank financial institution, organized neatly in the form of a company that berorentasi on the business aspect looks real in the modern era. The concept of sharia insurance provides an overview and offer that sharia insurance a breakthrough that comes from conventional insurance. Such exclusively sharia insurance has a lot of enthusiasts, especially for people who still lay. After the review, it is known that sharia insurance is implemented through mutual assistance mechanism to create harmony and stability in social life of the community. Sharia insurance as an instrument of investment and protection of property, and life, can good work by avoiding elements maisir, gharar, riba and risywah. Sharia insurance in principle has a difference with conventional insurance as well as a better altermatif against conventional insurance. Keywords : Sharia Insurance, Islamic Economics